Proximal Transverse Vaginal Septum In Women With Primary Infertility : A Rare Case Report - Rauzatul Jannah; Yusra Septivera; Rusnaidi Rusnaidi; Sarah Nainggolan (Surgical Residency Program Syiah Kuala University, 2026)
Introduction: A transverse vaginal septum (TVS) represents an uncommon congenital malformation of female genital structures resulting from incomplete canalization where the urogenital sinus meets the distal portion of Müllerian ducts. This condition occurs in approximately 1 per 2,100 to 1 per 72,000 female live births. TVS manifests as either obstructive or non-obstructive variants and frequently correlates with infertility and painful intercourse. Surgical intervention is necessary to reestablish normal vaginal structure and enhance fertility potential. Case description: This report details a 28-year-old female presenting with inability to conceive following 18 months of consistent unprotected marital relations. Her complaints included painful sexual activity, reduced menstrual flow, and menstrual cramping. Physical examination identified a dense transverse membrane in the proximal vaginal third, measuring roughly 2 cm in thickness, positioned 5 cm beyond the introitus, containing a tiny opening that obscured cervical observation. Sonographic evaluation demonstrated unremarkable uterine and adnexal structures. Hysterosalpingography could not be completed due to septal blockage. Surgical management included vaginal septal excision combined with diagnostic laparoscopy and chromopertubation, demonstrating normal reproductive organs with open fallopian tubes and endometrial implants on the uterine surface that underwent ablation. Patient recovery proceeded without complications. Conclusion: A transverse vaginal septum constitutes a rare congenital malformation potentially presenting with fertility difficulties and dyspareunia during reproductive years. Surgical removal with vaginal restoration represents the preferred therapeutic approach to reestablish normal anatomy and maximize reproductive potential. Continued postoperative surveillance is crucial for detecting complications and assessing fertility outcomes.